Peran Inflasi Dalam Memoderasi Makro Ekonomi Terhadap Indeks Harga Saham Gabungan (IHSG) - Liman, Shanny; Gisela, Stefany; Delvin, Delvin (Politeknik Ganesha Medan, 2024)
Investors can use the Composite Stock Price Index (IHSG) to see how a country's economy is trending and decide when they will buy and sell shares. However, movements in the Composite Stock Price Index (IHSG) are not only influenced by the macroeconomic situation in the country, but also by the world economy. This research seeks to quantify the influence/impact of the Exchange Rate, Interest (BI Rate), GDP, World Gold Prices and World Oil Prices on the Composite Stock Price Index (IHSG) on the Indonesian Stock Exchange with Inflation as a moderating variable for the period 2020 - 2022. In this research, the research used is quantitative descriptive research. By using documentation techniques and library methods, secondary data was collected for data collection for this research. The research population consisted of 36 data using a sampling method, namely saturated sampling. The data in this study was tested using a program known as SmartPLS 3.2.9. The data analysis technique is using the Partial Least Squares structural equation which is carried out using two-stage modeling and testing procedures. The results of this research explain that the exchange rate, interest (BI Rate), world gold prices and world oil prices do not have a significant impact on the Composite Stock Price Index (IHSG). Meanwhile, GDP has a positive and significant impact on the IHSG. Inflation does not have the capability to moderate the relationship between exchange rates, interest (BI rate), GDP, world gold prices and world oil prices on the Composite Stock Price Index (IHSG)